2021
DOI: 10.1001/jamasurg.2021.1425
|View full text |Cite
|
Sign up to set email alerts
|

All-Cause and Cancer-Specific Death of Older Adults Following Surgery for Cancer

Abstract: Cancer (RESTORE-Cancer) GroupIMPORTANCE Cancer care has inherent complexities in older adults, including balancing risks of cancer and noncancer death. A poor understanding of cause-specific outcomes may lead to overtreatment and undertreatment.OBJECTIVE To examine all-cause and cancer-specific death throughout 5 years for older adults after cancer resection. DESIGN, SETTING, AND PARTICIPANTSThis population-based cohort study was conducted in Ontario, Canada, using the administrative databases stored at ICES (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 88 publications
2
15
0
Order By: Relevance
“…The incidence of melanoma is not high, accounting for about 4% of malignant tumors, but its malignant degree is generally high; in particular, the survival rate of patients with advanced metastatic melanoma is low [ 2 4 ]. Melanoma accounts for more than 70% of skin cancer-related deaths [ 5 , 6 ]. Oral and maxillofacial malignant melanoma, which can occur in the skin or mucosa, is a relatively high degree of malignant tumor [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of melanoma is not high, accounting for about 4% of malignant tumors, but its malignant degree is generally high; in particular, the survival rate of patients with advanced metastatic melanoma is low [ 2 4 ]. Melanoma accounts for more than 70% of skin cancer-related deaths [ 5 , 6 ]. Oral and maxillofacial malignant melanoma, which can occur in the skin or mucosa, is a relatively high degree of malignant tumor [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor We read with great interest the study by Chesney et al 1 In this population-based cohort study using 8 health administrative databases in Ontario, Canada, among 82 037 older adults undergoing cancer surgery, 6443 (7.9%) had preopera-tive frailty and 55 491 (67.6%) experienced perioperative (preoperative and/or postoperative) chemotherapy or radiotherapy within 180 days before or after surgery. Of note, the results of this study identified that preoperative frailty was independently associated with cancer and noncancer deaths, while perioperative therapy was independently associated with noncancer death of older adults after cancer surgery.…”
Section: Associations Of Preoperative Frailty With Cancer and Noncanc...mentioning
confidence: 99%
“…If this variable of frailty or other variables closely associated with postoperative death were missing in some individual databases or some potentially important data for some patients were not recorded in these databases, how did the authors deal with the missing data? As we can see from eFigure 1 in Supplement 1 of this study, 1 only very few cases owing to missing data (n = 98) were excluded from this population-based cohort study (N = 87 086 for the whole cohort).…”
Section: Associations Of Preoperative Frailty With Cancer and Noncanc...mentioning
confidence: 99%
“…Breast cancer in older women was generally less aggressive and more indolent than in younger women. Meanwhile, a population-based cohort study conducted that the majority of death in older patients with early breast cancer were from causes like cardiovascular and cerebrovascular diseases other than breast cancer itself [ 2 ]. Therefore, de-escalating treatments for early-stage breast cancer has always been the treatment theme for aging patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%